2017
DOI: 10.3389/fpls.2017.00567
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Isoflavone Biosynthesis by miRNAs in Two Contrasting Soybean Genotypes at Different Seed Developmental Stages

Abstract: Owing to the presence of nutritionally important, health-promoting bioactive compounds, especially isoflavones, soybean has acquired the status of a functional food. miRNAs are tiny riboregulator of gene expression by either decreasing and/or increasing the expression of their corresponding target genes. Despite several works on identification and functional characterization of plant miRNAs, the role of miRNAs in the regulation of isoflavones metabolism is still a virgin field. In the present study, we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 79 publications
(88 reference statements)
2
28
0
Order By: Relevance
“…38.9-and 101.4-fold, 5.9 and 84.3-fold, respectively (Figure 12b,c). In agreement with the previous studies, our results also showed the lower accumulation of RA-Mid region than the RA 3 0 region signifying that these target genes are potentially cleaved by corresponding regulatory miRNAs (Oh et al, 2008;Gupta et al, 2017). Our combinatorial approach of fusing two different miRNA identification softwares with two types of deep-sequencing data from same platform in clusterbean provides a systematic overview on novel and known miRNAs expression profiling involved in galactomannan biosynthesis.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…38.9-and 101.4-fold, 5.9 and 84.3-fold, respectively (Figure 12b,c). In agreement with the previous studies, our results also showed the lower accumulation of RA-Mid region than the RA 3 0 region signifying that these target genes are potentially cleaved by corresponding regulatory miRNAs (Oh et al, 2008;Gupta et al, 2017). Our combinatorial approach of fusing two different miRNA identification softwares with two types of deep-sequencing data from same platform in clusterbean provides a systematic overview on novel and known miRNAs expression profiling involved in galactomannan biosynthesis.…”
Section: Discussionsupporting
confidence: 91%
“…38.9‐ and 101.4‐fold, 5.9 and 84.3‐fold, respectively (Figure b,c). In agreement with the previous studies, our results also showed the lower accumulation of RA‐Mid region than the RA 3′ region signifying that these target genes are potentially cleaved by corresponding regulatory miRNAs (Oh et al ., ; Gupta et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The methodologies for quantification and data analysis of different isoforms of isoflavone were adopted from our previous publication (Gupta et al, 2017).…”
Section: Pcr Amplification Of Bisulfite-treated Dna Sequencing and mentioning
confidence: 99%